Effect of calcination temperature on photocatalytic degradation of polybrominated diphenyl ether compounds (PBDEs) over Ni/TIO2/PVC catalyst - Norsahida Azri; Rusmidah Ali; Wan Azelee Wan Abu Bakar (Pusat e-pembelajaran, UMS, 2022)
Polybrominated diphenyl ether compounds (PBDEs), widely used as flame retardants in household products, have been identified as organic pollutants with elevated ecological risk due to their toxicity, persistence, bioaccumulation and global distribution. In the present work, the photodegradation of PBDEs under UV light with Ni/TiO2/PVC was investigated under the influence of different calcination temperatures (700, 800 and 900°C). The characteristics of the catalyst were analysed by X-ray diffraction (XRD).